2002
DOI: 10.1093/intqhc/14.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Use of home health services covered by new public long-term care insurance in Japan: impact of the presence and kinship of family caregivers

Abstract: The use of major services may be decided more by the needs of caregivers than by the care level of the applicant. To successfully implement the new system, consideration of the caregiver situation should be included in policy making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Among these, the indirect costs related to the family caregivers are extremely relevant [24] and may even further affect the effectiveness of any domiciliary program, especially in those individuals who are totally home bound or confined to bed. Indeed, it has been calculated that the use of major services and resources may be decided more by the needs of caregivers than by the care level of the applicant [29]. Additionally, the estimation of the costs for initiating domiciliary ventilation is missing; indeed, it could also be important to calculate how many patients have to try the equipment before the staff finds the patient who really accepts the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the indirect costs related to the family caregivers are extremely relevant [24] and may even further affect the effectiveness of any domiciliary program, especially in those individuals who are totally home bound or confined to bed. Indeed, it has been calculated that the use of major services and resources may be decided more by the needs of caregivers than by the care level of the applicant [29]. Additionally, the estimation of the costs for initiating domiciliary ventilation is missing; indeed, it could also be important to calculate how many patients have to try the equipment before the staff finds the patient who really accepts the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Japan described the use of welfare and healthcare services by older community-dwellers who had applied for long-term care insurance, most of whom required personal assistance in daily activities. Of 237 participants with care-givers, only 22% did not use any kind of service, and more than one-third used two or more services (9). In Europe, the proportion of older disabled persons who received home-care services ranged from 24% in Denmark to less than 4% in Italy, Spain and Portugal (2,10).…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of public long-term care insurance in April 2000 and changes in legislation provide disincentives for longer hospitalization and encourage the frail elderly to be discharged earlier. Tamiya et al (2002) reported that the use of home services covered by long-term care insurance was determined by the needs of caregivers rather than by the care needs of the applicant. More home services were used in the case of a wife caring for her husband.…”
Section: Discussionmentioning
confidence: 99%